(untitled) (Journal of Social Sciences Review, 2023)
In the recent era of globalization, organizations need to avoid it, and environmental destruction has become an enormous challenge, especially when organizations face problems of environmental degradation. Because of this, researchers have paid considerable attention to understanding key determinants of green creativity (GC), an emerging area in the fields of sustainability and organizational behavior. Supporting social learning theory, this study examines the effect of spiritual leadership on employees’ green creativity through the mediating mechanism of employee environmental commitment (EEC). Rationally, this study follows a post-positivist device and thus implements a quantitative research design approach. Multilevel data was collected from 405 employees working in universities and hospitals in Pakistan. Multilevel path analysis is applied by using Mplus. Our research reveals that spiritual leadership (SL) has a statistically positive effect on employee environmental commitment, which ultimately increases green creativity (GC). This research offers several solutions to save energy by turning off extra lights, garbage, and recycling so that we can overcome the losses we face in our daily lives.